How to you solve 1-(2/5 + 1/5) N/A
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write1,493 answers
starTop subjects are Science, Social Sciences, and History
A general rule is to always solve what is in the parenthesis first. Here you are adding 2/5 to 1/5. The answer would be 3/5. Now you are going to take the first part of the equation which is 1 and subtract 3/5. Your answer would be 2/5.
Say for example the parenthesis said (6/15 - 1/5). In this case you would need to find a common denominator which in this case it is 15. You want the denominators to be the same....
(The entire section contains 2 answers and 226 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- Solve the equation n! + (n+1)! = (n+2)!.
- 1 Educator Answer
- Solve the expression ( n +1 )!/( n-1)! = 30
- 1 Educator Answer
- 5/6·1/2+2/3÷4/3 How do I solve this problem?
- 1 Educator Answer
- How do you solve for n? n/33=19
- 3 Educator Answers
- (a) Use Definition 2 to find an expression for the area under the curve y= (x^3) from 0 to 1 as a...
- 1 Educator Answer
calendarEducator since 2009
write35,413 answers
starTop subjects are History, Literature, and Social Sciences
1-(2/5 + 1/5)
Lets take 1-(2/5 + 1/5)=x
Therefore, x= 1-(2/5 + 1/5)
In order to solve any Math problem, we need to always keep in mind the BODMAS rule. Therefore, in this problem, we first solve the brackets by taking L.C.M. of the values inside the bracket and adding them up, and so on.
x=1-{(2+1)/5}
x=1-(3/5)
We convert 3/5 into decimal form:
x=1-0.6
x=0.4 or x=2/5
To solve the addition or subtracion of fractions you have to convert all the fractions with the equivalent fractions with the same or equal denominators.
Go for the bracketted expression, where the two terms could be added in the numerator as both has the same or equal denominator 5. You can add the numerator and retain the denominator. So 2/5+1/5 = (2+1)/5 =3/5.
Next step:
1-(2/5+1/5) = 1-3/5.
convert 1 and 3/5 int equivalent fractions of same denominator:
1 = 1/1 = 1*5/(1*5) =5/5. Therefore,
1-3/5 = 5/5-3/5 = (5-3)/5 = 2/5
first add 2/5 + 1/5 which is 3/5. Then take 1, or 5/5 - 3/5 and the answer is 2/5.
Suppose the probable figure is x
x= 1-(2/5+1/5)
or, x=1-{(2+1)/5}
or, x=1-3/5
or, x= (5-3)/5
or, x=2/5
So, the answer is 2/5. (Ans.)
Student Answers